The anthropology of performance : a reader - Korom, Frank J. (Hoboken : John Wiley & Sons Inc., 2013)
"The Anthropology of Performance" is an invaluable guide to this exciting and growing area. This cutting-edge volume on the major advancements in performance studies presents the theories, methods, and practices of performance in cultures around the globe. Leading anthropologists describe the range of human expression through performance and explore its role in constructing identity and community, as well as broader processes such as globalization and transnationalism.
Sadržaj: Part 1: Performance in prehistory and antiquity ; Part 2: Verbal genres of performance ; Part 3: Ritual, drama, and public spectacle ; Part 4: Performance and politics in the making communities ; Part 5: Tourist performances and the global ecumene
Bibliografija: str. [273]-285.
Bibliograf. bilješke uz poglavlja.
Stvarno kazalo
Keywords: performans - antropološki aspekt; kulturalna antropologija; sociologija kulture